Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of iron content of boric acid, boric oxide, $7Idi$7Rsodium tetraborates, sodium perborates and crude sodium borates Part 17, (28th February 1979) - British Standards Institution,
No abstract available